The Biocompatibility of eugenol after an intraosseous implantation - Al-Sarraf M. Khulood (College of Pharmacy / Mustansiriyah University, 2006)
The biocompatibility of the Eugenol, as one of the commonest root canal filling (RCF), material was evaluated through an intraosseous implantation of this material in the mandible of the Syrian hamsters. Forty Syrian hamsters were divided into 5 groups, 8 animals in each group, group 1 as control, and group 2, 3, 4, 5 as experimental groups. After the animal was anesthetised, the skin was reflected and a hole of 2mm. diameter X 2mm. depth was drilled in all the hamster mandibles. A mixture of Eugenol and Zinc oxide as a paste was placed in that hole of each animal of the experimental groups and left for different periods, 7 days, 14 days, 21 days, and 28 days. After the hamsters were sacrificed, a histological examination of the implantation site was performed, the results showed that Eugenol elicited a severe inflammatory reaction at day 7, and this inflammatory reaction is increased to become more severe at day 14, and the reaction begin to  decrease with the 21 day giving about the same histopathological picture of after 7 days to become moderate after 28 days. Our conclusion is that the Eugenol is a biologically irritant material even after 4 weeks of its intraosseous implantation.